Protecting Data in Modern Computing Devices (International Journal of Engineering and Computer Science, 2016)
The modern era is moving towards computing devices that have a high degree of mobility. The drawbacks from the security features that has to be handled is that mobile devices need to be power conscious and it can also be easily stolen due to less weight and small form factor. Due to limited power availability the amount of cryptographic computation should be minimized as these consume more power. The other major drawback from the security angle on physically missing the compute device, the data stored in both dynamic and static storage of the device can be retrieved by unauthorized persons leading to breach of privacy and confidentiality. This paper explains the modern compute device mechanisms using which the privacy and confidentiality concerns be addressed with limited amount of usage of cryptographic functions. The limited usage of cryptographic functions also has an advantage of low battery consumed.